Labeling and tracking of immune cells in ex vivo human skin - Dijkgraaf, Feline E.; Toebes, Mireille; Hoogenboezem, Mark; Mertz, Marjolijn; Vredevoogd, David W.; Matos, Tiago R.; Teunissen, Marcel B. M.; Luiten, Rosalie M.; Schumacher, Ton N. (Nature protocols, 2021)
Human skin harbors various immune cells that are crucial for the control of injury and infection. However, the current understanding of immune cell function within viable human skin tissue is limited. We developed an ex vivo imaging approach in which fresh skin biopsies are mounted and then labeled with nanobodies or antibodies against cell surface markers on tissue-resident memory CD8 + T cells, other immune cells of interest, or extracellular tissue components. Subsequent longitudinal imaging allows one to describe the dynamic behavior of human skin-resident cells in situ. In addition, this strategy can be used to study immune cell function in murine skin. The ability to follow the spatiotemporal behavior of CD8 + T cells and other immune cells in skin, including their response to immune stimuli, provides a platform to investigate physiological immune cell behavior and immune cell behavior in skin diseases. The mounting, staining and imaging of skin samples requires ~1.5 d, and subsequent tracking analysis requires a minimum of 1 d. The optional production of fluorescently labeled nanobodies takes ~5 d. This protocol describes how to follow the behavior of immune cells by imaging ex vivo cultured human or mouse skin biopsies following labeling with antibody or nanobody reagents against specific cell surface markers.